2017
DOI: 10.1007/s11747-017-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

Customer engagement in service

Abstract: We develop a framework to facilitate customer engagement in service (CES) based on the service-dominant (S-D) logic. A novel feature of this framework is its applicability and relevance for firms operating both in developed and emerging markets. First, we conduct a qualitative study involving service managers from multinational companies (MNCs) across the developed and emerging markets to understand the practitioner viewpoints. By integrating the insights from the interviews and the relevant academic literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
337
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(365 citation statements)
references
References 92 publications
(118 reference statements)
14
337
1
13
Order By: Relevance
“…We challenge Hollebeek et al's (2016a, p. 6) contention of engagement as a volitional (voluntary) concept (Kumar et al, 2017), which while potentially applicable to many customer contexts (e.g. in free market settings), may not common for other ecosystem actors (e.g.…”
Section: Theoretical Foundations: S-d Logic Structuration Theory and Ementioning
confidence: 63%
“…We challenge Hollebeek et al's (2016a, p. 6) contention of engagement as a volitional (voluntary) concept (Kumar et al, 2017), which while potentially applicable to many customer contexts (e.g. in free market settings), may not common for other ecosystem actors (e.g.…”
Section: Theoretical Foundations: S-d Logic Structuration Theory and Ementioning
confidence: 63%
“…As Hollebeek et al (2019) point out, emotions do not just drive purchase, but they are inherently communicative. We find substantial effects of emotions on sharing behavior, which is considered an important articulation of customer engagement (Kumar et al 2019). In order for managers to utilize these insights it is important to adjust their marketing dashboards to include more fine-grained measures of emotions.…”
Section: Managerial Implicationsmentioning
confidence: 91%
“…From a customer experience management perspective, it is important to consider a holistic view that explicitly includes emotional responses of consumers (Kranzbühler et al 2018). Recent research also stresses the importance of such emotional responses in relation to factors that drive consumer engagement (e.g., Hollebeek et al 2019;Kumar et al 2019), to the point that they are considered more impactful than cognitive evaluations (Hollebeek et al 2019). As Hollebeek et al (2019) point out, emotions do not just drive purchase, but they are inherently communicative.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The concept of customer brand engagement (CBE) is gaining increased momentum within the hospitality branding literature (King, Sparks, & Wang, 2016;Leckie, Nyadzayo, & Johnson, 2016;Rather, Hollebeek, & Islam, 2019;So, So, King, & Sparks, 2014). The individual customers' interaction with the brands is characterized by specific levels of cognitive, emotional and behavioral activities (Kumar, Rajan, Gupta, & Dalla Pozza, 2017;Rather, 2018). Previous empirical research reported that consumer-brand engagement can lead to customer loyalty and increase the profitability for the business (Aaker, Fournier, & Brasel, 2004;Bowden, 2009;Brodie, Ilic, Juric, & Hollebeek, 2013;Leckie et al, 2016;Rather, 2019;So, King, Sparks, & Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%